PENGEMBANGAN MEDIA ULAR TANGGA “ASIK” DALAM MENINGKATKAN AKTIVITAS FISIK PADA SISWA KELAS IV MADRASAH IBTIDAIYAH (Jurnal Kesehatan Siliwangi, 2021)
This research is motivated by the lack of learning media regarding physical activity. The learning process uses books and video media, other alternative media are still rarely used. Therefore, the snake and ladder media "Physics Activity" was created as an alternative media in increasing physical activity. The purpose of this study was to find out the right media and to find out the average and difference in pulse rates before and before using the "Physics Activity" snake and ladder media. This research method uses the ADDIE development model which consists of 5 stages, including: analysis, design, development, implementation and evaluation. The results of the validation of the "Physics Activity" snake and ladder media by material experts stated that the media was very feasible/very valid to use and media experts stated that the media was feasible/valid to use. The design of this study used a one group pre test post test design without control on 34 students of class IV MI Cibolang Kidul. This study calculates the pulse before and after playing the "Physics Activity" snake and ladder game. Data analysis using univariate obtained mean pulse before intervention 83 and after 116 and bivariate analysis with Wilcoxon test at 0.05. The results of data analysis showed a significance value of 0.000 <0.05, it is certain that the snake and ladder media "Physics Activity" can increase the pulse of the fourth grade students of MI Cibolang Kidul by 39.75%.